Sirius: Retrofitting Brutalism in Sydney. (June 2019) - Gandh, V; North, ML
Abstract: The Sirius building in Sydney, Australia has and continues to be at the centre of contestations pertaining to its proposed sale, possible demolition, and redevelopment of the site. The ostensibly Brutalist building erected between 1975 and 1980 was built to accommodate public housing tenants, as were a number of other such buildings in different parts of the world built during post-World War II, as Brutalism was seen to represent an ethical architecture through its expression and aesthetic. With 79 apartments of 1-4 bedrooms, and of in-situ and precast concrete construction, Sirius is being upheld as an excellent example of Brutalism, and opposition to the proposed sale and redevelopment of the site has been mounted on the basis that the building should be heritage listed for its historic, social, technical and aesthetic significance. The argument of saving the building on the basis that it houses public housing tenants has also been rigorously employed. At the same time the sale of the building has been justified on the basis that its retention would cause undue economic hardship to the owners by limiting funds for reinvestment in social housing elsewhere. This paper while acknowledging both sides of this debate, will seek to explore whether the retention of Sirius can be undertaken through refurbishment and retrofitting. Other such examples of Brutalist public housing in countries like the United Kingdom which have been retrofitted will form the basis of comparison to examine whether retrofitting of the Sirius will uphold its ethical dimension, or whether its retention will serve a market of consumers with an interest in mid-century architecture and design.